Approaches to Teaching Self-Advocacy Skills in Specialized Undergraduate Programs For Autistic College Students - Imoro, Abdul-Hakeem (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2025)
This study examined how faculty who teach in specialized undergraduate programs for autistic college students approach self-advocacy teaching. Test et al.’s (2005) conceptual framework of self-advocacy was used as a lens to investigate this topic. Through ten semi-structured interviews, seven themes emerged to address two research questions: (a) improve students’ learning skills; (b) support students’ career development; (c) improve students’ executive functioning skills; (d) improve students’ transition skills, (e) use flexible classrooms to support students; (f) support students’ skills development; and (g) develop students’ self-awareness skills. The discussions highlight the challenges, approaches, and conceptual implementations of the findings, within the broader literature, on faculty approaches to students' development of self-advocacy skills.